PERANCANGAN SISTEM APLIKASI PENGADUAN WARGA BERBASIS ANDROID DI KELURAHAN CIMONE - Prayogo Prayogo (LPPM Unbaja, 2023)
As the use of information technology advances, every government agency should try to improve the quality of its services. One of them is in the complaint service which is a place or forum for the public to express complaints, grievances, aspirations and appreciation of the Government's performance in accordance with Presidential Regulation Number 76 of 2013 concerning the management of public service complaints. This research takes a case study in Cimone Village, where there is no system for managing citizen complaints, especially in Cimone Village. To anticipate residents spreading their complaints in the wrong place, without knowing how to submit complaints correctly. For this reason, there is a need for an Android-based citizen complaint application system as a space for aspirations that can be accessed easily. The application design uses the Waterfall method, built using Android Studio, the Java programming language and Firebase as the database, and the system testing uses black box testing so that the Android-based citizen complaint application system fulfills the aspirations of Cimone sub-district residents in a relevant and flexible manner.